Baqadamawi Haylaselase zamana mangest, ye Eritria guday : 1941-1963 - Zawde Rata, 1935- (Addis Ababa : Shama books, 2006)
On how Eritrean issues were handled during the reign of Emperor Haile Sellasie.
Includes bibliographical references (p. 541-543)
In Amharic.